Public enterprise in mixed economies : some macroeconomic aspects - Floyd, Robert H.; Gray, Clive S.; Short, R. P.; International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1984)
The three papers in this volume reflect a view that analysis of the macroeconomic situation in countries with significant public enterprise sectors is enhanced by examining, among other things, the operations of the sector as a whole, or any industrial grouping therein, or even individual enterprises with sufficient weight to exercise a perceptible impact on macroeconomic parameters.
Includes bibliographical references.
hza 02/08/2018
Loans
Keywords: Government business enterprises; Mixed economy